ANALISIS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DAN SWOT DI SDN 2 UBUNG KOTA DENPASAR - Erik Sanjaya, I Putu; Arta, I Gede Dharma Surya; Suardana, I Gede; Chindytia; Abadi, Ida Bagus Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) at SD Negeri 2 Ubung, Denpasar, and identify the school’s strengths, weaknesses, opportunities, and threats through a SWOT analysis. Using a descriptive mixed-methods approach, data were collected through structured observation instruments, in-depth interviews, and documentation studies involving the principal, teachers, and school committee. The results show that the implementation of SBM at SD Negeri 2 Ubung is in a “Good” category, supported by visionary and participatory leadership from the principal, strong curriculum management through the Merdeka Curriculum, active student management through various extracurricular activities including archery, and transparent financial management through BOS funds. Regarding the SWOT analysis, key strengths include structured academic programs and the “7 Habits of Excellent Indonesian Children” program; weaknesses include uneven student literacy levels and infrastructure limitations; opportunities include government support and community engagement; while threats include teacher shortages and funding constraints. This study recommends strengthening digital archiving, expanding external partnerships, and enhancing the principal’s supervisory role to achieve accountability and sustainable educational quality.